Surgery versus surveillance for ascending aortic aneurysms in elderly patientsCentral MessagePerspective - Veronica F. Chan, BSc; Ming Hao Guo, MD, MSc; Thais Coutinho, MD; Aryan Ahmadvand, BSc; Mahdi Zeghal, BSc; Adam Mussani, BSc; Talal Al-Atassi, MD, MPH; Roy Masters, MD; David Glineur, MD, PhD; Munir Boodhwani, MD, MSc (JTCVS Open)
Background: Whether elderly patients with aortic root or ascending aortic aneurysm (ATAA) would benefit from the new surgical size threshold of 5.0 cm is unknown. This study aimed to evaluate the natural history of ATAA in elderly patients and to compare long-term outcomes of those who underwent initial surveillance versus surgery. Methods: Patients age ≥75 years with an ATAA ≥40 mm were categorized into 2 groups: initial surgery and initial surveillance. The primary outcome was all-cause mortality; Kaplan-Meier curves were plotted for survival. A multivariable Cox proportional hazard regression model was used to identify independent predictors of long-term mortality. Results: The study series comprised 300 patients, including 58 who underwent initial surgery and 242 who received surveillance between July 2010 and September 2022. In the surveillance cohort, the mean aneurysm growth rate was 0.10 cm/year. Comparing surveillance to surgery, at 8 years there was no difference in survival (mean, 77.8 ± 3.4% vs 71.8 ± 9.6%; P = .65). For 116 patients with an initial aneurysm diameter ≥5.0 cm, there was no difference in survival between the 2 groups at 8 years (76.5 ± 7.0% vs 68.4 ± 11.3%; P = .20). Larger body surface area (hazard ratio [HR], 1.44; 95% confidence interval [CI], 1.09-1.90; P = .01) and history of smoking (HR, 2.25; 95% CI, 1.27-3.98; P = .01) were identified as predictors of long-term mortality. Conclusions: In our series of elderly patients with ATAA, there was no difference in 8-year survival between initial surveillance and surgical management, with a high competing risk of nonaortic mortality. Surveillance may be a reasonable alternative to surgery for selected older adults with ATAA <5.5 cm.